A retrospective study on the effects of diabetes mellitus on perioperative fibrinogen and bleeding amount in coronary artery bypass surgery patients (Annals of Medical Research, 2021)
None
Keywords: Diabetes Mellitus; Cardiopulmonary Bypass; Fibrinogen; Bleeding Amount.